2002
DOI: 10.4049/jimmunol.168.11.5811
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Dependent Prostaglandin E2 Production Is Regulated by the Glutathione-Dependent Prostaglandin E2 Synthase Gene Induced by the Toll-Like Receptor 4/MyD88/NF-IL6 Pathway

Abstract: Macrophages produce a large amount of PGE2 during inflammation. This lipid mediator modulates various immune responses. PGE2 acts on macrophages and inhibits production of cytokines such as TNF-α and IL-12. Membrane-bound glutathione-dependent PGE2 synthase (mPGES) has been shown to be a terminal enzyme of the cyclooxygenase-2-mediated PGE2 biosynthesis. Here we identified mPGES as a molecule that is induced by LPS in macrophages. The expression of mPGES was not induced by LPS in mice lacking Toll-like recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
224
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(247 citation statements)
references
References 33 publications
19
224
1
1
Order By: Relevance
“…Although these effects of PGE 2 on the immune system have been known for several years, the role of PGE 2 during infections is just starting to be examined. Recent studies show that bacterial components LPS, CpG DNA, and peptidoglycan wall can all induce COX-2 expression and PGE 2 production (21,22,25). Interestingly, L. pneumophila and Escherichia coli both use PGE 2 to modulate T cell function (31,63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these effects of PGE 2 on the immune system have been known for several years, the role of PGE 2 during infections is just starting to be examined. Recent studies show that bacterial components LPS, CpG DNA, and peptidoglycan wall can all induce COX-2 expression and PGE 2 production (21,22,25). Interestingly, L. pneumophila and Escherichia coli both use PGE 2 to modulate T cell function (31,63).…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of PG on the immune system are understood, their role in infectious disease is not. Recent studies have clearly demonstrated that the bacterial products LPS, peptidoglycan, and CpG DNA can initiate COX gene up-regulation and PG secretion (21)(22)(23)(24)(25). Thus, bacterial infections that can induce PGE 2 are able to inhibit T cell function, and should gain an advantage in in vivo growth.…”
mentioning
confidence: 99%
“…The temporal and spatial properties of PGE 2 synthesis are determined by the regulated expression of each of the enzymes involved in this cascade. Of the several putative PGES that have been described, mPGES1 is the best characterized, and a role for mPGES1 in inflammation and febrile responses has been clearly demonstrated (21,32,33). Although mPGES1 is expressed in the kidney (17)(18)(19)34), its contribution to PGE 2 synthesis in the kidney and to the consequent regulation renal functions has not been characterized previously.…”
Section: Discussionmentioning
confidence: 99%
“…One of the nuclear targets in the TLR-mediated signaling pathway is NF-IL6, a member of the C/EBP family of transcription factors (Tanaka et al, 1995). NF-IL6 was originally identified as a transcription factor that specifically binds to an IL-1 responsive element in the IL-6 gene promoter (Akira et al, 1990), and was subsequently shown to play an important role in LPS-induced gene expression in macrophages (Gorgoni et al, 2001;Uematsu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%